고령의 단계적 양측 고관절부 골절의 임상적 형태분석 - 고덕환(Duk-Hwan Kho); 신주용(Ju-Yong Shin); 김형준(Hyeung-June Kim); 김동헌(Dong-Heon Kim) (The journal of the Korean Orthopaedic Association, 2009)
목 적: 고령의 환자에서 시간적 차이가 있는 양측성 고관절부 골절 환자에 있어서, 단계적 양극성 반치환술 시행 후 임상적 형태를 분석하여 문헌 고찰과 함께 보고하고자 한다. 대상 및 방법: 1999년 3월부터 2005년 12월까지 시간적 차이가 있는 양측성 고관절부 골절로 단계적 양극성 반치환술을 시행한 75세 이상 고령의 환자 중, 2년 이상 추시 가능하였던 21명을 대상으로 보행능력, 일상 생활 활동능력, 골절 원인 및 형태, 동반 질환 및 관절 증상 등을 분석하여 임상적 평가와 방사선적 평가를 시행하였다. 결 과: 선행 골절 18예, 이차 골절 14예에서 수술 전 보행능력을 회복하였고, 기본 생활 활동능력은 선행 골절 14예, 이차 골절 14예에서 가능하였다. 이차 골절의 수상 원인은 실족 20예, 낙상 1예였다. 동반 관절 증상은 요통 14예, 내반 변형 슬관절염 11예, 견관절염 8예, 무지 외반증 5예였고, 동반 질환은 심혈관계 질환 16예, 당뇨 11예, 뇌혈관 질환 8예, 폐질환 3예였다. 다른 선행 골절 병력은 요추 압박 골절 11예, 족관절 골절 6예, 요골 원위부 골절 5예, 골반 치골지 골절 2예였다. 결 론: 고령의 시간적 차이가 있는 양측성 고관절부 골절의 임상적 형태 연구에서 실족과 낙상의 예방이 중요하였고, 이를 위해 치료 가능한 동반 질환 및 동반 관절 증상에 대한 예방적 치료가 필요하다고 사료된다. Purpose: We wanted to evaluate the clinical features after treating of bilateral sequential hip fractures in the elderly. Materials and Methods: We reviewed the clinical records of 21 patients who were older than 75 years and who underwent bilateral bipolar hemiarthroplasty for sequential hip fractures between March 1999 and November 2005. The minimum follow up period was 2 years. We analyzed the results by conducting radiological and clinical evaluations such as assessing the patient’s walking ability, the activities of daily living, the mechanism of fracture and the associated medical conditions and arthritis. Results: Walking ability was recovered by 18 cases of primary fracture and by 14 cases of sequential fracture. Return to the activities of daily living was achieved by 14 cases of primary fracture and by 14 cases of sequential fracture. The fracture mechanism was a fall/slip in 20 cases and a fall from a height in 1 case. The associated arthritis was in the spine in 14 cases, the knee in 11 cases, the shoulder in 8 cases and Hallux valgus in 5 cases, and the associated medical conditions were mainly urge incontinence in 17 cases and cardiovascular disease in 16 cases. The other previous fractures were spine compression fracture in 11 cases, ankle fracture in 6 cases, distal radius fracture in 5 cases and pelvic ramus fracture in 2 cases. Conclusion: Preventing recurrent falls plays a role in preventing bilateral sequential hip fractures. We think that the treatment of curable associated medical conditions and arthritis is necessary to prevent recurrent falls. KCI Citation Count: 1